Effectiveness of the Team-Based Learning method in the teaching and learning in Physiotherapy (Research, Society and Development, 2022)
Health education requires adequate articulation between methods and contents for the development of fundamental competences for care practice. In this context, Team-Based Learning (TBL) is a methodology that allows the student to apply knowledge in a sequence of activities to the achievement of learning objectives. The aim of this study was to evaluate the effectiveness of TBL in the teaching and learning process in a Physical Therapy course. This is a quantitative-qualitative study with a sample of students and professors of the Physical Therapy course of a higher education institution in the state of Goiás, Brazil, and application of the TBL methodology and conduction of focus groups. Data from sample characterization and TBL performance were analyzed in EpiInfo® and SPSS® software using Wilcoxon's test and Spearmam's correlation (p < 0.05). The audio transcripts of the focus groups were analyzed using content analysis in the MAXQDA Analytics Pro® software. The performance of the student sample (n = 207) in the TBL was correlated with age and means of transport. The factors mentioned with a positive influence on the educational process were: 1) construction of knowledge and criticality; 2) comparison between TBL and the traditional teaching model; 3) improvement in learning; 4) student motivation; 5) commitment and role of the teacher; and 6) relationship between professor and student. TBL proved to be an effective strategy for large groups. However, the need for greater prior teaching planning and the reduced institutional support hamper the use of this methodology.